Mechanochemical Approach to Carbon Nanotubes-Based Piezoresistive Sensors’ Fabrication - Elisabetta Primiceri; Anna Grazia Monteduro; Francesco Montagna; Maria Serena Chiriacò; Francesco Ferrara; Mariaenrica Frigione; Giuseppe Maruccio; Antonio Turco (Proceedings)
The development of 3D porous nanocarbon composites has improved the performance of piezoresistive sensors. However, the functionalization and surface distribution of nanocarbon may limit conductivity and mechanical stability. In this study, a mechanochemical approach was developed to create an elastomeric/CNTs 3D porous nanocomposite. By changing parameters such as CNT length and polymer amount, different composites with improved piezoresistive properties can be produced for wearables or fluidic devices. The material can withstand compressive stress up to 150 Kpa and has a sensitivity of up to 330 Kpa−1 and a limit of detection of 0.2 Pa and 50 nm for pressure and extension, respectively.